Investigation on antimicrobial activity of biomass components of Cerbera odollam - S. F. Sulaiman (Universiti Sains Malaysia, 2015)
This research investigates the antibacterial actlvlty of different parts of biomass components of Cerbera odollam. Methanol extracts from different part of Cerbera odollam were prepared and further fractionated using n-hexane, ethyl acetate and ethanol. Obtained fractions were tested against both Gram-positive and Gramnegative bacteria (Bacillus subtilis, Bacillus licheniformis, Escherichia coli and Pseudomonas aeruginosa) for their antibacterial activity. Hexane soluble parts from flower, fruit, leaf, wood, bark and ethyl acetate soluble parts from bark showed antibacterial activity against Bacillus subtilis. Hexane soluble parts from leaf and bark and ethyl acetate soluble parts from wood showed antibacterial activity against Bacillus licheniformis. All of the extracts and fractions showed no antibacterial activity against Escherichia coli and Pseudomonas aeruginosa.